Mental health, quality of life, wellbeing, loneliness and use of social media in a time of social distancing during the COVID-19 outbreak. A cross-country comparative study. (4th March 2021) - Geirdal, Amy Østertun; Ruffolo, Mary; Leung, Janni; Thygesen, Hilde; Price, Daicia; Bonsaksen, Tore; Schoultz, Mariyana
Abstract: Background: The COVID-19 outbreak raised questions about how people experience their mental health, quality of life (QoL), wellbeing and loneliness in the context of social distancing, and the use of social media during this time Aims: To examine the experience of mental health, QoL, wellbeing and loneliness and use of social media among people living in Norway, USA, UK and Australia. Methods: A cross-country comparative survey of people living in Norway, USA, UK and Australia. Relevant statistical analyses were used to examine differences between the countries and to explore associations between demographic, mental health and psychosocial variables and use of social media. Results: There were 3810 respondents from four countries, of which 50 − 74% showed a high level of emotional distress. The Norwegian population reported significantly better mental health, QoL and wellbeing and lower levels of loneliness compared to the other countries. High-frequent use of social media after the COVID-19 outbreak was associated with poorer mental- and psychosocial health. Conclusions: The results suggest that the COVID-19 outbreak took a toll on people's experience of mental health, QoL, wellbeing and experienced loneliness, and high-frequent use of social media was associated with these factors.